2017
DOI: 10.1038/s41598-017-16054-5
|View full text |Cite
|
Sign up to set email alerts
|

Invasive plants as potential food resource for native pollinators: A case study with two invasive species and a generalist bumble bee

Abstract: It is now well established that invasive plants may induce drifts in the quantity and/or quality of floral resources. They are then often pointed out as a potential driver of bee decline. However, their impact on bee population remains quite unclear and still controversial, as bee responses are highly variable among species. Here, we compared the amino acid composition of pollen from three native and two invasive plant species included in diets of common pollinators in NW Europe. Moreover, the nutritional inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…We can test how variations in the P:L values of pollen species affect bee physiology and health in the lab and field [20]; more sophisticated geometric framework studies [10] are clearly needed for different bee species. Pollen nutrition may also be important for understanding invasive ecology and responses to climate change [19,50,86,87]. For instance, introduced bees may adapt to new geographic regions by shifting to host-plant species with phylogenetically conserved pollen nutrition (Vaudo et al in prep).…”
Section: Applying Pollen P:l In the Futurementioning
confidence: 99%
“…We can test how variations in the P:L values of pollen species affect bee physiology and health in the lab and field [20]; more sophisticated geometric framework studies [10] are clearly needed for different bee species. Pollen nutrition may also be important for understanding invasive ecology and responses to climate change [19,50,86,87]. For instance, introduced bees may adapt to new geographic regions by shifting to host-plant species with phylogenetically conserved pollen nutrition (Vaudo et al in prep).…”
Section: Applying Pollen P:l In the Futurementioning
confidence: 99%
“…If exotic plant species could alter mountain bee assemblages, this may have significant effects on pollination of native plant species. Since their effect could vary depending on which bee species is considered, some native bee species could benefit from the introduction of exotic plants, as providers of additional resources ( Tepedino, Bradley & Griswold, 2008 ; Drossart, Michez & Vanderplanck, 2017 ). Nonetheless, it has been recently demonstrated that the introduction of exotic plants could be even more problematic that changes in the landscape, affecting not only insect assemblages but also complete plant-pollinator networks ( Hansen et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, more than 64% of naturalized exotic plants in Europe are found in industrial areas, 58.5% in farmland and parks and gardens, 37.5% in lawns, and 31.5% in woods and forests [184]. In the context of highly forage-depleted environments associated with human activities, invasive plant species can provide, in some cases, valuable food resources for generalist pollinators and restore/enhance ecological functions such as pollination [69,81,[185][186][187]. For instance, in Ohio, USA, Trifolium repens and Trifolium pratense help to restore wild bee populations in urban areas ( [188,189].…”
Section: Dealing With Invasive Alien Speciesmentioning
confidence: 99%